Proteomic analysis of diabetic retinas - Starr, Christopher R.; Zhylkibayev, Assylbek; Mobley, James A.; Gorbatyuk, Marina S. (Frontiers in Endocrinology, 2023)
Introduction As a metabolic disease, diabetes often leads to health complications such as heart failure, nephropathy, neurological disorders, and vision loss. Diabetic retinopathy (DR) affects as many as 100 million people worldwide. The mechanism of DR is complex and known to impact both neural and vascular components in the retina. While recent advances in the field have identified major cellular signaling contributing to DR pathogenesis, little has been reported on the protein post-translational modifications (PTM) - known to define protein localization, function, and activity - in the diabetic retina overall. Protein glycosylation is the enzymatic addition of carbohydrates to proteins, which can influence many protein attributes including folding, stability, function, and subcellular localization. O-linked glycosylation is the addition of sugars to an oxygen atom in amino acids with a free oxygen atom in their side chain (i.e., threonine, serine). To date, more than 100 congenital disorders of glycosylation have been described. However, no studies have identified the retinal O-linked glycoproteome in health or disease. With a critical need to expedite the discovery of PTMomics in diabetic retinas, we identified both global changes in protein levels and the retinal O-glycoproteome of control and diabetic mice. Methods We used liquid chromatography/mass spectrometry-based proteomics and high throughput screening to identify proteins differentially expressed and proteins differentially O-glycosylated in the retinas of wildtype and diabetic mice. Results Changes in both global expression levels of proteins and proteins differentially glycosylated in the retinas of wild-type and diabetic mice have been identified. We provide evidence that diabetes shifts both global expression levels and O-glycosylation of metabolic and synaptic proteins in the retina. Discussion Here we report changes in the retinal proteome of diabetic mice. We highlight alterations in global proteins involved in metabolic processes, maintaining cellular structure, trafficking, and neuronal processes. We then showed changes in O-linked glycosylation of individual proteins in the diabetic retina.